2021
DOI: 10.20944/preprints202111.0074.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isochoric Specific Heat in the Dual Model of Liquids

Abstract: We continue in this paper to illustrate the implications of the Dual Model of Liquids (DML) by deriving the expression for the isochoric specific heat as function of the collective degrees of freedom available at a given temperature and analyzing its dependence on temperature. Two main tasks will be accomplished. First, we show that the expression obtained for the isochoric specific heat in the DML is in line with the experimental results. Second, the expression will be compared with the analogous one obtained… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 43 publications
(203 reference statements)
1
7
0
Order By: Relevance
“…We will return on the calculation of V C in Section 3.3, where an expression for V C is determined in the frame of DML. In a separate paper [54] the dependence on temperature of V C is analysed and it is shown that the theoretical expression obtained in the DML is in line with the experimental results; besides, its comparison with the analogous one obtained in the PLT model allows to get interesting insights about the number of collective degrees of freedom available in a liquid and on the value of the isobaric thermal expansion coefficient. A limitation of the PLT is that this model only deals with intermolecular modes and neglect intramolecular ones; DML tries to cover this gap with the aid of the parameter ' m ', accounting for the statistical number of DoF actually excited at the considered thermodynamic state (see Eq.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…We will return on the calculation of V C in Section 3.3, where an expression for V C is determined in the frame of DML. In a separate paper [54] the dependence on temperature of V C is analysed and it is shown that the theoretical expression obtained in the DML is in line with the experimental results; besides, its comparison with the analogous one obtained in the PLT model allows to get interesting insights about the number of collective degrees of freedom available in a liquid and on the value of the isobaric thermal expansion coefficient. A limitation of the PLT is that this model only deals with intermolecular modes and neglect intramolecular ones; DML tries to cover this gap with the aid of the parameter ' m ', accounting for the statistical number of DoF actually excited at the considered thermodynamic state (see Eq.…”
supporting
confidence: 52%
“…( 20), that deserves a dedicated analysis because it has many interesting consequences. In a separate paper [54] it has been compared with the expression given by PLT model [11,[29][30][31][32][33][34][35][36][37][38] for the same physical quantity. The Authors calculate an expression for the harmonic and anharmonic contributions to the specific heat within a liquid phonon theory based on the concept of liquid relaxation time introduced by Maxwell [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations